Do princípio de conservação de energia mecânica: uma proposta de ensino da física no ensino médio - Hermida, Raimundo Fredson Maciel (2019)
This paper is part of an investigation of how the obstacles to learning are overcome by the concept of Conservation of Mechanical Energy, organized through the support of Classical and contemporary authors that deal with learning, knowledge construction, didactic transposition. and the formation of the scientific spirit such as: Barchelard, Chavellard, PCN's, BNCC, Gabriel Dias, Lucia Helena among others, we seek to analyze and demonstrate the process of teaching - learning of a concept, in the context of regular school education, from the analysis of data extracted from SADEAM (Educational Performance Evaluation System of Amazonas) in 2012 and 2015 that pointed to a learning deficit of the chosen concept. After applying a questionnaire that updated and confirmed the permanence of the difficulty, a schedule of activities was elaborated considering the pedagogical assumptions that allow us to produce a supporting text linked to a didactic sequence with which it was possible to notice substantial progress in the acquisition and verbalization of the contents. addressed in this, as an alternative proposal for the teacher and student who may have interest in this.